2020
DOI: 10.30605/25409190.186
|View full text |Cite
|
Sign up to set email alerts
|

Need Analysis of English Material for Vocational School of Health: A Case Study at One School at Karanganyar

Abstract: This research aims to identify the students’ prospective professional need in learning English writing skills, to identify the style of learning that students preferred in learning English writing skills, and to reveal the incompetent that students need to improve in writing. This study required stratification that minimizes sampling errors to zero level. In this study, the 140 students from the second grade were chosen to be the participant. The questionnaire was used to be instruments to get the responses fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…Sari & Wirza (Sari, F. P., & Wirza, 2021) also found that there are still many cases where vocational schools do not implement ESP in their teaching-learning process even though their students need to focus on English related to their major and job desk needs. , schools need to fulfill students' need to improve their proficiency in ESP as Vongvilay et al, (Vongvilay, P., Kartika, D., & Laila, 2020) found that rather than general English, the pupils' preferred subject for studying is the subject of health. Students also need to develop their ability to expand an idea in writing and learn English independently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sari & Wirza (Sari, F. P., & Wirza, 2021) also found that there are still many cases where vocational schools do not implement ESP in their teaching-learning process even though their students need to focus on English related to their major and job desk needs. , schools need to fulfill students' need to improve their proficiency in ESP as Vongvilay et al, (Vongvilay, P., Kartika, D., & Laila, 2020) found that rather than general English, the pupils' preferred subject for studying is the subject of health. Students also need to develop their ability to expand an idea in writing and learn English independently.…”
Section: Discussionmentioning
confidence: 99%
“…First, a study by Sari & Wirza (2021) reflects that there are still many cases where vocational schools do not implement ESP in their teaching-learning process even though their students need to focus on English related to their major and job desk needs. Second, a study by Vongvilay et al (2020) discovered that small-group instruction is the best way for students to learn how to write in English. Then, rather than general English, the pupils' preferred subject for studying is the subject of health.…”
Section: Figure 1 Need Analysis Cyclical In Esp Processmentioning
confidence: 99%
“…From these various studies, it can be concluded that all efforts to plan and develop the learning, including the development of questions, must begin with a needs analysis. The results of the needs analysis reveal the main considerations to be made to meet the needs of students and teachers (Mahbub, 2018;Ratri & Puspitasari, 2019;Onas, Nurhayati, & Mukmin, 2022;Vongvilay, Kartika, & Laila, 2020;Yundayani, Emzir, & Rafli, 2017). Similarly, the needs analysis can also identify the problems occurring to the students and teachers, knowledge or skills, expectations and media that are desired in the learning process.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have examined the need analysis relating to ESP in the design of curricula or the result of materials at a certain level of education in Indonesia. Rahamdina, Harahap & Sofyan (2019), Vongvilay, Kartika & Laila (2020), Azizah, Inderawati & Vianty (2020), Septiana, Petrus, & Inderawati (2020), Kumbara, Eryansyah, & Inderawati (2021). In other countries such as Kayaoglu and Akbas (2016), Lee (2016), Alsamadani (2017), Chetsadanuwat (2018), andWu &Low' (2018).…”
Section: Introductionmentioning
confidence: 99%